Unionisation Structures and Innovation Incentives - Justus Haucap; Christian Wey (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper examines how different unionisation structures affect firms' innovation incentives and industry employment. We distinguish three modes of unionisation with increasing degree of centralisation: (1) 'Decentralisation' where wages are determined independently at the firm-level, (2) 'coordination' where one industry union sets individual wages for all firms, and (3) 'centralisation' where an industry union sets a uniform wage rate for all firms. While firms' investment incentives are largest under 'centralisation', investment incentives are non-monotone in the degree of centralisation: 'Decentralisation' carries higher investment incentives than 'coordination'. Labour market policy can spur innovation by decentralising unionisation structures or through non-discrimination rules.
urn:nbn:de:gbv:705-opus-1581
Keywords: L13; K31; J50; D43; 330; Duopol; Tarifpolitik; Lohnverhandlungstheorie; Investition; Arbeitsproduktivität; Innovation; Theorie